Tantangan Pelibatan Keluarga dalam Meningkatkan Life Skill Anak Penyandang Disabilitas Di Sekolah Luar Biasa (SLB) Pembina Kabupaten Gayo Lues - Nurul Hidayati Nurul; Sa'i Sa'i (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2023)
A challenge is something that is felt to be unusual that must be faced and resolved. Challenges can be felt by anyone, including parents who have children with disabilities. Children with disabilities have the right to receive education in special special education schools. Apart from education at school, children with disabilities must also receive education at home provided by their families, especially their parents. The family is the smallest unit that plays an important role in providing care and education for children, but some parents feel that the responsibility for children's education is only given by the school. The aim of this research is to determine the challenges of involving families in improving the life skills of children with disabilities at the Special School (SLB) Pembina Gayo Lues district and the role of parents in improving the life skills of children with disabilities. This research uses qualitative research methods with a descriptive approach. The data collection techniques used in this research are observation, interviews and documentation. This research found several challenges faced by families including: (1) Consistent and appropriate parenting patterns for children with disabilities, (2) Higher psychological pressure in caring for children with disabilities, (3) Parental maturity in educating children with disabilities . The role of parents in improving the life skills of children with disabilities includes: (1) The role of parents in providing alternative education services to children with disabilities, (2) The role of parents in meeting the needs of children with disabilities and (3) The role of parents in providing social support for children with disabilities.